Polypharmacy including falls risk-increasing medications and subsequent falls in community-dwelling middle-aged and older adults - Kenny, Rose (My University, 2015)
Background: polypharmacy is an important risk factor for falls, but recent studies suggest only when including medications associated with increasing the risk of falls. Design: a prospective, population-based cohort study. Subjects: 6,666 adults aged ≥50 years from The Irish Longitudinal study on Ageing. Methods: participants reported regular medication use at baseline. Any subsequent falls, any injurious falls and the number of falls were reported 2 years later. The association between polypharmacy (>4 medications) or fall risk-increasing medications and subsequent falls or injurious falls was assessed using modified Poisson regression. The association with the number of falls was assessed using negative binomial regression. Results: during follow-up, 231 falls per 1,000 person-years were reported. Polypharmacy including antidepressants was associated with a greater risk of any fall (adjusted relative risk (aRR) 1.28, 95% CI 1.06–1.54), of injurious falls (aRR 1.51, 95% CI 1.10–2.07) and a greater number of falls (adjusted incident rate ratio (aIRR) 1.60, 95% CI 1.19–2.15), but antidepressant use without polypharmacy and polypharmacy without antidepressants were not. The use of benzodiazepines was associated with injurious falls when coupled with polypharmacy (aRR 1.40, 95% CI 1.04–1.87), but was associated with a greater number of falls (aIRR 1.32, 95% CI 1.05–1.65), independent of polypharmacy. Other medications assessed, including antihypertensives, diuretics and antipsychotics, were not associated with outcomes. Conclusion: in middle-aged and older adults, polypharmacy, including antidepressant or benzodiazepine use, was associated with injurious falls and a greater number of falls.
PUBLISHED
Cited By :3 Export Date: 28 August 2015
Keywords: falls older people polypharmacy drug therapy; falls older people polypharmacy drug therapy; Ageing